2018
DOI: 10.1590/1678-4162-10027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on cardiovascular parameters in search and rescue-trained dogs

Abstract: Physical activity alters the cardiovascular system of dogs, depending on the exercise characteristics and the animal’s physical conditioning. Little is known about the cardiovascular changes in rescue-trained dogs. This study evaluated the cardiovascular responses to a search and rescue exercise session to differentiate these alterations from cases of exhaustion or some possible pathology. Nine healthy rescue-trained dogs that trained for at least one year were used. Seven German Shepherds and two Belgian Shep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Recently, the use of human heart rate monitors for the measurement of dogs' heart rates [12,[17][18][19] has become preferred to the gold standard, i.e., electrocardiography (ECG) [20,21]. Such monitors consist of a chest strap with electrodes and a built-in signal transmitter.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of human heart rate monitors for the measurement of dogs' heart rates [12,[17][18][19] has become preferred to the gold standard, i.e., electrocardiography (ECG) [20,21]. Such monitors consist of a chest strap with electrodes and a built-in signal transmitter.…”
Section: Discussionmentioning
confidence: 99%
“…2 Adequate training is essential for successful maximal physical conditioning; it could avoid exercise-related problems that can result in critical downtime and compromise its career. 2,29,57,60 Dogs that are routinely trained for sports and working reasons could benefit from the effective and efficient way of improving physical capacity with the aid of HIIT methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac adaptations secondary to a physical activity routine also trigger cardiac remodeling in dogs (Civelek et al, 2012;Santos et al, 2018), and electrocardiography (ECG) changes consistent with this condition can be observed, such as an increase in QRS duration, QT interval, and S wave amplitude (Bavegems et al, 2009;Constable et al 2000). In time, significant alterations to the electrocardiographic exam were observed in military service dogs after a six-week physical training process, where the electrocardiogram revealed physiological adaptations at a cardiovascular level triggered by the practice of physical activity (Moraes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In time, significant alterations to the electrocardiographic exam were observed in military service dogs after a six-week physical training process, where the electrocardiogram revealed physiological adaptations at a cardiovascular level triggered by the practice of physical activity (Moraes et al, 2017). Moreover, the "athlete's heart" syndrome was described in search, rescue, and recovery dogs due to the physical activity routine, but without electrocardiographic changes (Santos et al, 2018). A study using electrocardiography in several breeds of dogs identified that German Shepherds presented arrhythmias the most (Noszczyk-Nowak et al, 2017); also, such breed is widely used by military services (Ferworn, 2009;Lima et al, 2016).…”
Section: Introductionmentioning
confidence: 99%